Education (Bildung) and Creative Writing “Becoming What One Is” in Diverse Possible Worlds - Saavedra Rey, Sneider (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The invention nof possible worlds implied by literary criticism enables new forms of existence motivated by fiction. For a pedagogy of literature, it is necessary to reflect about the idea of education (Bildung) aspiritual self realization where persons transcend their immediate reality and surpass the proposed educational meanings, discovering and travelling through unknown places inside themselves, in a process of personal growth. This article is derived from doctoral research that relates these two concepts Bildung and creative writing from their aesthetic dimension, as significant constructions of new ways of living and being, until developing a proposal of literary education based on fiction writing as an inner unfolding that allows for the exploration of the human condition, contrary to the marginality of this type of work in the educational system.